Sustainability in the Supply Chain: Analyzing the Role of the Focal Company and Training in the Implementation of SDGs - Teixeira, Talita Borges [UNESP]; Battistelle, Rosane A. G. [UNESP]; Teixeira, Adriano Alves [UNESP]; Bonacina, Camila Zanchettin [UNESP]; Vitoreli, Marinez Cristina [UNESP] (MDPI, 2022)
Understanding how training can contribute to employee awareness, development of skills, competencies, and knowledge of the implementation of the Sustainable Development Goals (SDGs) in supply chains and the role of the focal company still remains unanswered. Thus, this article had the purpose of investigating the performance of a company in the Brazilian electricity sector in the implementation of the Sustainable Development Goals (SDGs) in the supply chain. A review of the literature on the SDGs and the importance of focal companies and training for their execution was carried out in order to theoretically support the study. Then, the case study technique was used to understand “how” and “which” training practices are being implemented in the supply chain to make the management of the SDGs more effective. The results indicate: (i) that the systematic application of training by the focal company is crucial for the implementation of SDGs in the supply chain, (ii) that the focal company plays an important role in leading the implementation of the SDGs in the supply chain, and (iii) that the partnerships between supply chain members are important and facilitate sustainable management in the supply chains. Additionally, we present a robust set of training practices conducted in the supply chain and the results achieved.
Keywords: 2030 Agenda; Brazil; emerging economy; focal company; sustainability in supply chains; Sustainable Development Goals; training